2023
DOI: 10.1111/cas.15826
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic benefit of comprehensive genomic profiling in clinical practice remains uncertain

Abstract: The overall survival of patients who received genomically matched therapy was not significantly longer than that of patients receiving treatment only other than genomically matched therapy in the breast invasive ductal carcinoma (A), colorectal adenocarcinoma (B), and pancreatic adenocarcinoma (C) cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…CGP testing is now used as multiple companion diagnostics to search for treatment options for patients with advanced cancer, and 7.8% of patients who underwent CGP testing received genomically matched therapy based on the detected variants 28 . In fact, no difference in efficacy between molecularly targeted therapy and conventional chemotherapy has been demonstrated, and the prognostic benefit of CGP in clinical practice remains uncertain 35,36 . In addition to companion diagnostics, CGP testing is also used for patient stratification based on data on hundreds of mutations for which there is currently no genetically matched therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CGP testing is now used as multiple companion diagnostics to search for treatment options for patients with advanced cancer, and 7.8% of patients who underwent CGP testing received genomically matched therapy based on the detected variants 28 . In fact, no difference in efficacy between molecularly targeted therapy and conventional chemotherapy has been demonstrated, and the prognostic benefit of CGP in clinical practice remains uncertain 35,36 . In addition to companion diagnostics, CGP testing is also used for patient stratification based on data on hundreds of mutations for which there is currently no genetically matched therapy.…”
Section: Discussionmentioning
confidence: 99%
“… 28 In fact, no difference in efficacy between molecularly targeted therapy and conventional chemotherapy has been demonstrated, and the prognostic benefit of CGP in clinical practice remains uncertain. 35 , 36 In addition to companion diagnostics, CGP testing is also used for patient stratification based on data on hundreds of mutations for which there is currently no genetically matched therapy. The present study, which demonstrated that mutation profiles can predict survival and response to drug therapy for STS, may provide impetus to the use of mutation profiles.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 , 6 , 7 Although the ratio of druggable mutations diagnosed in CGP tests is still small, some reports showed an improved prognosis when treatment based on genomic abnormalities was available. 8 , 9 As limited treatment options of conventional cytotoxic chemotherapeutic agents are currently available for unresectable pancreatobiliary cancers, many patients with pancreatobiliary cancers undergo CGP testing to expand their treatment options such as BRCA1/2 in pancreatic cancer, 10 FGFR2 fusion in biliary tract cancer, 11 , 12 and microsatellite instability‐high and tumor mutational burden‐high in solid tumors. 13 …”
Section: Introductionmentioning
confidence: 99%